Safety and tolerability of repetitive transcranial magnetic stimulation in patients with pathologic positive sensory phenomena: A review of literature - Muller, Paul A.; Pascual-Leone, Alvaro; Rotenberg, Alexander (Brain stimulation, 2012)
Repetitive transcranial magnetic stimulation (rTMS) is emerging as a valuable therapeutic and diagnostic tool. rTMS appears particularly promising for disorders characterized by positive sensory phenomena that are attributable to alterations in sensory cortical excitability. Among these are tinnitus, auditory and visual hallucinations, and pain syndromes. Despite studies addressing rTMS efficacy in suppression of positive sensory symptoms, the safety of stimulation of potentially hyperexcitable cortex has not been fully addressed. We performed a systematic literature review and metaanalysis to describe the rTMS safety profile in these disorders. Using the PubMed database, we performed an English-language literature search from January 1985 to April 2011 to review all pertinent publications. Per study, we noted and listed pertinent details. From these data we also calculated a crude per-subject risk for each adverse event. One hundred six publications (n = 1815) were identified with patients undergoing rTMS for pathologic positive sensory phenomena. Adverse events associated with rTMS were generally mild and occurred in 16.7% of subjects. Seizure was the most serious adverse event, and occurred in three patients with a 0.16% crude per-subject risk. The second most severe adverse event involved aggravation of sensory phenomena, occurring in 1.54%. The published data suggest rTMS for the treatment or diagnosis of pathologic positive sensory phenomena appears to be a relatively safe and well-tolerated procedure. However, published data are lacking in systematic reporting of adverse events, and safety risks of rTMS in these patient populations will have to be addressed in future prospective trials.